Vibration characteristic responses due to transient mass loading on wind turbine blades. (August 2019) - Al-Hadad, Mohammed; McKee, Kristoffer K.; Howard, Ian
Abstract: Wind turbine blades can experience mass collision events during operations, either due to bird strikes or with other flying objects. The rapid impact loadings due to these events can cause fatigue damage leading to subsequent blade loss or even wind turbine system failure. This paper addresses the effects of transient loadings resulting from a rapid mass reduction event from the rotating blade as well as an impacting mass onto the wind turbine blade, leading to transient vibration and unbalance within the turbine system. The novelty of the research is that it shows the coupling between the blade in-plane with tower transverse ( Z -direction) vibrations, and blade out-of-plane with tower front (Y-direction) vibrations which have been identified through different experiments. Measurements from an experimental small-scale horizontal axis wind turbine test rig are reported, instrumented with contact and non-contact sensors and rotating and non-rotating sensors, to investigate the various transient impact loading events. Additionally, the drive shaft vibration for different conditions has been monitored by utilizing orthogonal laser measurement for detecting the main shaft displacements towards perpendicular axes. Subsequent orbit analysis is presented showing the analysis of different shaft orders during the rapid mass reduction and mass collision events. Complex orbit and filtering analysis of shaft orders during the transient mass impact loading events are used to demonstrate the sensitivity of the sensors for further fault detection. Highlights: Evaluation of rotating and non-rotating sensors for wind turbine applications. Transient mass loading of rotor blades detected from blade strain. Significant coupling between the rotor, main shaft and tower vibration components. Orbit analysis of shaft and tower vibration detects transient mass loading.